Positive solutions for a Hadamard-type fractional p-Laplacian integral boundary value problem - Xu, Yihui; Wang, Feng; O'Regan, Donal; Xu, Jiafa (Nonlinear Analysis: Modelling and Control, 2024)
In this paper we study the existence of positive solutions to a Hadamard-type fractional integral boundary value problem using fixed point index. We construct a new linear operator and obtain our main results under some conditions concerning the spectral radius of this linear operator. Our method improves and generalizes some results in the literature.